2016
DOI: 10.1021/acs.inorgchem.6b00075
|View full text |Cite
|
Sign up to set email alerts
|

Solid State Collapse of a High-Spin Square-Planar Fe(II) Complex, Solution Phase Dynamics, and Electronic Structure Characterization of an Fe(II)2 Dimer

Abstract: Square-planar high-spin Fe(II) molecular compounds are rare, and until recently, the only four examples of non-macrocyclic or sterically driven molecular compounds of this kind shared a common FeO4 core. The trianionic pincer-type ligand [CF3-ONO]H3 (1) supports the high-spin square-planar Fe(II) complex {[CF3-ONO]FeCl}{Li(Sv)2}2 (2). In the solid state, 2 forms the dimer complex {[CF3-ONO]Fe}2{(μ-Cl)2(μ-LiTHF)4} (3) in 96% yield by simply applying a vacuum or stirring it with pentane for 2 h. A detailed high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…In this particular ground state configuration, the asymmetry in charge distribution caused by the additional electron in the d z 2 orbital is compensated by ligand field contributions from the four ligands in the xy -plane resulting in a near radially symmetric electric field gradient at the iron nucleus. Veige and co-workers have suggested that small values of |Δ E Q | can be considered a fingerprint of square-planar high-spin Fe II . , This proposal was further supported by data from Limberg and co-workers and is consistent with earlier studies of the electronic structure of the iron sites in gillespite. , …”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…In this particular ground state configuration, the asymmetry in charge distribution caused by the additional electron in the d z 2 orbital is compensated by ligand field contributions from the four ligands in the xy -plane resulting in a near radially symmetric electric field gradient at the iron nucleus. Veige and co-workers have suggested that small values of |Δ E Q | can be considered a fingerprint of square-planar high-spin Fe II . , This proposal was further supported by data from Limberg and co-workers and is consistent with earlier studies of the electronic structure of the iron sites in gillespite. , …”
Section: Resultssupporting
confidence: 75%
“…Veige and co-workers have suggested that small values of |ΔE Q | can be considered a fingerprint of square-planar high-spin Fe II . 27,28 This proposal was further supported by data from Limberg and co-workers 26 and is consistent with earlier studies of the electronic structure of the iron sites in gillespite. 51,52 Inspired by the unusual electronic structure of ( Mes PDP Ph )-Fe(OEt 2 ), the synthesis of ( Mes PDP Ph )FeL complexes with other L-type ligands was investigated.…”
Section: ■ Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…More recently, however, a number of molecular compounds containing high-spin square planar FeL 4 arrangements in a non-strained environment were presented, suggesting that specific ligand environments may inherently electronically stabilize a square planar over a tetrahedral structure. [27][28][29][30][31] In ref. 27 the preference for a square planar structure was rationalized with the help of DFT calculations, as a Jahn-Teller (JT) flattening of the usual FeL 4 tetrahedron, caused by four highly charged, π-basic ligands L. In the present work this explanation will be further explored in the specific context of α-Fe in a zeolite environment, making use of a combined DFT/CASPT2 approach.…”
Section: Introductionmentioning
confidence: 99%